Theoretical Modeling of Room Shape for Ray Tracing Simulation. Issue 1 (March 2014) - Hoshi, Kazuma; Hanyu, Toshiki
With the recent developments in computer-aided design (CAD) technology, the detailed modeling of shapes has become routine. However, it is well known that low-frequency sounds do not propagate in detail-oriented models of rooms in the way that is predicted by geometrical acoustic simulations. Therefore, rough models of room shapes are commonly used and scattering coefficients are set for each material in this kind of simulation. However, scattering coefficients are difficult to use for creative room shape design, because scattering coefficients need to be measured in advance. Thus, we propose a new method for ray tracing simulations that can be used in place of the scattering coefficient method. This paper presents a discussion of methods for constructing the appropriate room shape for the analyzed frequency from a detail-oriented model of a room.